Common EU minimum standards for enhancing mutual admissibility of evidence gathered in criminal matters - Kusak, Martyna (European journal on criminal policy and research, 2017)
The EU, while developing instruments for evidence-gathering in criminal matters, is not making much of an effort to enhance its admissibility. This may lead to situations where, given the differences between legal systems across the EU, evidence collected in one member state will not be admissible in other member states. Due to the fact that the Lisbon Treaty opened the possibility of adopting minimum rules concerning, among other things, the mutual admissibility of evidence, this paper is dedicated to verifying whether it is feasible to achieve various common EU minimum standards for evidence-gathering.